PERBANDINGAN BACKBONE CURVE KOLOM MENGGUNAKAN METODE PENDEKATAN PERILAKU MEKANIS, XTRACT, DAN ASCE 41-17 TERHADAP HASIL EKSPERIMEN - Nisrina Luthfiyah; William Ansel; Wilnando Wilnando; Faza Muhammad Izbik Fika Mumtaz (LPPM Universitas Abdurrab, 2024)
The inelastic behavior of earthquake-resistant buildings is expected to be able to withstand the cyclic loads that occur due to earthquake loads. The inelastic behavior of a building can be seen from the force-displacement curve. The curve can be obtained using several approaches, but each approach can provide different values. In this study, a backbone curve will be constructed using three approaches, namely the analytical approach, XTRACT software, and the ASCE 41-17 method. The specimen under review is a rectangular column with a single cantilever test configuration. The review parameters were the type, spacing, and area of reinforcement as well as the axial force ratio. The backbone curve obtained is compared with the experimental backbone curve. Based on the analysis, it was found that the most conservative method was ASCE 41-17. Evaluation was conducted on the three approaches used and the parameters reviewed